Stabilizing quercetin and lipoate effect on enzymatic antioxidant system (glutathione peroxidase and glutathione reductase) in the retina during experimental diabetes treatment (Ukrainian Journal of Ophthalmology, 2026)
Introduction. The thesis actuality consists in studying the quercetin and lipoate effect during experimental diabetes treatment.Objective. To study the quercetin and lipoate effect on the antioxidant system enzymes, particularly, glutathione peroxidase and glutathione reductase during experimental diabetes.Material and methods. Researches were conducted on white rats. Experimental animals were divided into four groups: the first one – control group (14 rats); the second one – experimental group (14 rats), animals with developing diabetes, without drug administration; the third one – experimental group (12 rats), animals with developing diabetes and lipoic acid administration; the fourth one – experimental group (15 rats), animals with developing diabetes and quercetin administration. The activity of glutathione peroxidase and glutathione reductase was determined in homogenates of retinas and blood plasma.Results. The usage of thiol preparations and bioflavanoid considerably contributes to the stabilization of hydroperoxide neutralization processes in the retina in conditions of experimental diabetes. It is also required to specify that the effect of a thiol preparation – lipoic acid was more expressed as compared with quercetin.Conclusion. The effect of lipoic acid and quercetin preparations during the experimental diabetes (2 & 6 months) considerably allows avoiding the inhibition of antioxidant system enzymes in animal retina. It is confirmed by the increase of the activity of glutathione peroxidase in the retina when using lipoate by 65.0% (in 2 months) and by 74.3% (in 6 months), and glutathione reductase - by 26.7% (in 2 months) and by 34.4% (in 6 months) for the group of untreated animals. The quercetin injection increases the activity of glutathione peroxidase by 60.6% (in 2 months) and by 65.9% after six months, and glutathione reductase by 20.4 and 29.8% correspondingly. The most expressed effect for reducing the degree of damage of antioxidant system enzymes is specific for lipoic acid.
Keywords: streptozotocin-induced diabetes; retina; glutathione peroxidase; glutathione reductase; quercetin; lipoate; experiment